Corporate judo strategy: leveraging the power of a competitor’s change to grow your own business - Hostager, Todd J. (Henry Stewart Talks, 2014)
Mergers and acquisitions, Downsizing, Merger impacts on customers, Merger impacts on employees, Merger impacts on performance and profitability, Bottom line impacts, Corporate Judo, Judo strategy, Growth opportunity, Self-disruption, Turbulent change, Change management, Exploiting a competitor’s change, M&A myths, M&A truths, M&A facts and fictions, Track record of success, Value destruction, Corporate parenting, Synergy driven change, Bastien, Hostager & Miles, Michael Porter, Customer satisfaction, Customer dissatisfaction, Rival firms, Free market forces, Executive hubris, Managerial hubris, Track record of change, Worst case rumor mills, Information constipation, Fight flight, Timing and tactics, Waves of disruption, Fear and uncertainty, Customer losses, Layoffs, Cost cutting